Maqasid Sharia-Based Financial Plan to Prevent Conspicuous Consumption Among Muslim Household - Pusparini, Martini Dwi (Al-Tijary, 2022)
The trend of the flexing phenomenon, especially on social media, is currently causing various reactions, one of which is the tendency to consume and use various luxury facilities. In consumer behavior, this phenomenon is referred to as Conspicuous Consumption. In today's modern world, it happens not only to upper-class consumers, but also to everyone in the community with various goals, including the goals of acquiring social status, prestige, or wealth. For lower-middle households, of course, this is a problem, so financial planning is needed. This study aims to explore the perspective of Maqasid Sharia in financial planning for Muslim families as a solution to the Conspicuous Consumption phenomenon. This research is a qualitative descriptive study with a library research approach. Data were obtained from official reports as well as other literature from journals, books and websites. The results of this study indicate that financial planning based on the Maqasid Sharia hierarchy, namely Dharurriyah, Hajiyyah and Tahsiniyyah can prevent the phenomenon of Conspicuous Consumption in Muslim households. In addition, Islamic consumption which prohibits Israf and aims to achieve Maslahah is a contradiction to Conspicuous Consumption. Good financial planning will ultimately bridge Muslim families to achieve prosperity in this world and the hereafter. The study provides model that can be used to refine existing models and frameworks, thereby enhancing their effectiveness and applicability in real-world scenarios.